Regular and Young Investigator Award Abstracts 2020
DOI: 10.1136/jitc-2020-sitc2020.0179
|View full text |Cite
|
Sign up to set email alerts
|

179 Immunotherapy trials lack a biomarker for inclusion: implications for drug development

Abstract: BackgroundNext-generation sequencing and other biomarkers have demonstrated the capability to identify potentially pathogenic molecular aberrancies. Immune checkpoint inhibitors (ICI) have benefited patients in almost every oncologic histology. Combining these innovations has transformed how oncologists treat previously untreatable diseases.MethodsThe 413 trials from clinicaltrials.gov website were reviewed using the terms ‘nivolumab’ or ‘pembrolizumab’ between January 1, 2019 and December 31, 2019. Additional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Despite significant interest in the development of predictive biomarkers leveraging the systemic immune system, the vast majority of immunotherapy clinical trials are still performed without the use of a biomarker to guide inclusion 128 . Currently, there is no systemic immune biomarker that is sufficiently established to permit bedside decision-making, although some immunological features in the TME have been shown to be associated with prognosis in various contexts.…”
Section: Systemic Immune Biomarkers For Cancermentioning
confidence: 99%
“…Despite significant interest in the development of predictive biomarkers leveraging the systemic immune system, the vast majority of immunotherapy clinical trials are still performed without the use of a biomarker to guide inclusion 128 . Currently, there is no systemic immune biomarker that is sufficiently established to permit bedside decision-making, although some immunological features in the TME have been shown to be associated with prognosis in various contexts.…”
Section: Systemic Immune Biomarkers For Cancermentioning
confidence: 99%
“…Furthermore, a number of studies have recently shown that dendritic cells play a crucial role in the effectiveness of PD-L1 inhibition. (76)(77)(78)(79) Although specific immunological traits in the TME have been found to be related to prognosis in diverse circumstances, we still need an adequate systemic immune biomarker to be able to predict outcomes (80), and to support patient treatment decisions.…”
Section: Targeting Epigenetic Modifications In Cancer Therapymentioning
confidence: 99%
“…Mechanisms of primary and acquired resistance during treatment with immunotherapies remain to be elucidated. Patient selection and stratification based on relevant biomarkers has been substantially limited and near non-existent; a study of planned clinical trials in 2019 showed that less than 10 % of the studies required biomarkers for enrollment [22]. A very limited number of biomarkers are linked to higher chance of response to anti-PD(L)1-based immunotherapies at the population level, e.g., PD-L1 and tumor mutational burden (TMB) [23].…”
Section: Challenges In Development Of Combination Therapiesmentioning
confidence: 99%